Establishing Total Phosphorus Boundaries to Support Good Ecological Status of Greek Lakes and Reservoirs in Accordance with the Water Framework Directive - Zioga, M.; Kemitzoglou, D.; Zerva, Ι.; S. Katsavouni; I.Kagalou; Tsiaoussi, V. (2025)
Water. 2025: 17(23):3349. https://doi.org/10.3390/w17233349.